SKRINING POTENSI ANTIBAKTERI EKSTRAK ETANOL BUAH NANGKA MUDA (ARTOCARPUS HETEROPHYLLUS LAMK.) TERHADAP BAKTERI PENYEBAB DIARE - Umi Yuniarni (JURNAL FARMASI GALENIKA, 2014)
Empirically young jackfruit can treat acute diarrhea . This study aims to investigate the antibacterial activity of ethanol extracts young jackfruit against Escherichia coli and Shigella dysenteriae which causes diarrhea .Antibacterial activity test performed by the agar diffusion method at concentrations of 50, 75, 100 and 125 mg/mL and tetracycline was used as a standard. Thin layer chromatography was conducted to determine the marker compounds of young jackfruit.Minimum Iinhibitory Concentration (MIC) value of ethanol extract of young jackfruit against E. coli of 1.25 mg/mL and 2.5 mg/mL against S. dysenteriae .Young jackfruit ethanol extract at a concentration of 50 mg/ml comparable to tetracycline 36.30 mg/mL for E. coli and 35.48 mg/mL against S. dysenteriae.Ethanol extract of young jackfruit positive contribution to group phenolic compounds which pink flouresensed under 366nm UV and gave black color spot with FeCl3 at value of Rf 0.77.Ethanol extract of young jackfruit gave antibacterial activity against Escherichia coli and Shigella dysentriae and showed the content of phenolic compounds with Rf value of 0,77.